Synthesis and Electron-Transporting Properties of N-Type Polymers with Cardanol-Based Side Chains - Jin Cheng; Hongyu Fu; Yifan Qiao; Xuming Xue; Pirada Sudprasert; Kenji Ogino (Micromachines)
We synthesized n-type polymers poly{[N,N′-bis(2-octyldodecyl)-naphthalene-1,4,5,8-bis(dicarboximide)-2,6-diyl]-alt-5,5′-(2,2′-bithiophene)} [P(NDI2OD-T2)] and poly{[N,N′-bis(3-(4-cardanol)propyl)-naphthalene-1,4,5,8-tetracarboxylic diimide]-alt-[5,5′-bis(2-thienyl)-2,2′-bithiophene]} [P(NDICL-T2)] with cardanol-based side chains via Stille coupling to enhance electron mobility. Replacing the 2-octyldodecyl side chain with cardanol in P(NDICL-T2) improved electron mobility due to increased chain flexibility and ordered packing. Lower glass transition temperature (tg), red-shifted UV-vis absorption, results from crystalline structure analysis, indicating tighter lamellar spacing and enhanced molecular ordering, and smoother surface morphology confirmed the enhanced intermolecular interactions and uniform film formation.